KAJIAN TIPOLOGI SIGNAGE RUANG LUAR DI LINGKUNGAN PENDIDIKAN (Studi Kasus : Kawasan Kampus Universitas Nusa Cendana) - Lodwik O. Dahoklory (Universitas Negeri Gorontalo, 2023)
ABSTRACT. Signage as a wayfinding component provides its users with inside information to assist the navigation process within the built environment. Its role varies and determined by the type of built environment where the signage is located. Signage is designed for various purposes and types, in addition to its various roles. This article describes the findings related to the typology of signage in the educational settings. This study aimed to identify the typology of signage in the campus area of Nusa Cendana University. This study is a qualitative descriptive study that focus on outdoor signage in the campus area. Therefore, the study was conducted through literature study, observation, documentation, and identification of existing signage. The results of this study shows variety of signage types in the campus area based on their function and installation. Keywords: signage typology, outdoor signage, campus area ABSTRAK. Signage sebagai komponen wayfinding menyediakan informasi dalam bagi penggunanya untuk mempermudah proses navigasi dalam lingkungan binaan. Perannya beragam dan ditentukan oleh jenis lingkungan binaan dimana signage berada. Dengan peran yang beragam, signage dirancang dengan jenis dan tujuan yang beragam pula. Tulisan ini menjelaskan temuan terkait dengan tipologi signage di lingkungan pendidikan. Tujuan dari kajian ini adalah untuk mengidentifikasi tipologi signage dalam kawasan kampus Universitas Nusa Cendana. Kajian ini merupakan kajian deskriptif kualitatif dengan fokus pada signage ruang luar dalam kawasan kampus. Kajian dilakukan melalui studi pustaka, pengamatan langsung, dokumentasi dalam pengumpulan data dan identifikasi signage eksisting . Hasil dari kajian ini menunjukan ragam jenis signage dalam kawasan kampus berdasarkan fungsi dan pemasangannya. Kata kunci: tipologi signage, signage ruang luar, kawasan kampus.